2005
DOI: 10.1007/s10646-003-6367-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Bacteria Isolated from an Oligotrophic Lake with Pesticide Removal Capacities

Abstract: We studied the growth and capacities for pesticides removal of bacterial strains isolated from the Laguna Grande, an oligotrophic lake at the South of Spain (Archidona, Málaga). Strains were isolated from water samples amended with 10 and 50 microg/ml of nine pesticides: organochlorinated insecticides (aldrin and lindane), organophosphorous insecticides (dimetoate, methyl-parathion and methidation), s-triazine herbicides (simazine and atrazine), fungicide (captan) and diflubenzuron (1-(-4-chlorophenyl)-3-(2,6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 29 publications
0
35
0
1
Order By: Relevance
“…The purported abilities of various Aeromonas spp. include heavy-metal reduction, oil biodegradation (by producing surfactant to emulsify hydrocarbons, thereby facilitating degradation by a microbial consortium) (47), pesticide removal (63), and selenite reduction (45,83). In addition to the efflux transporters mentioned above, other CDSs in the genome may encode enzymes for the alteration of toxic compounds and facilitate the environmental stability of A. hydrophila.…”
Section: Vol 188 2006mentioning
confidence: 99%
“…The purported abilities of various Aeromonas spp. include heavy-metal reduction, oil biodegradation (by producing surfactant to emulsify hydrocarbons, thereby facilitating degradation by a microbial consortium) (47), pesticide removal (63), and selenite reduction (45,83). In addition to the efflux transporters mentioned above, other CDSs in the genome may encode enzymes for the alteration of toxic compounds and facilitate the environmental stability of A. hydrophila.…”
Section: Vol 188 2006mentioning
confidence: 99%
“…This fact confers substantial interest to the genus as a potential model system for the investigation of attributes that may correlate with adaptation and evolution of organisms to diverse thermal regimes (Vishnivetskaya et al, 2009). Several studies have shown that some strains of Exiguobacterium possess unique properties of interest for applications in biotechnology, bioremediation, industry and agriculture (Pattanapipitpaisal et al, 2002;Lopez et al, 2005;Okeke et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…natatoria and M. luteus are commonly isolated from moist environments. M. luteus is environmentally ubiquitous and is found in biofilms of aquatic ecosystems (8,35), in soil (54), and on human and animal skin (17,29). Cells of M. luteus are gram positive, coccus shaped, arranged in clusters of tetrads, and nonmotile.…”
mentioning
confidence: 99%